2018
DOI: 10.3847/2041-8213/aaab57
|View full text |Cite|
|
Sign up to set email alerts
|

Strong CO+ and Emission in Comet C/2016 R2 (Pan-STARRS)*

Abstract: We report on imaging and spectroscopic observations of comet C/2016 R2 (Pan-STARRS) obtained with the 0.8 m and 2.7 m telescopes of McDonald Observatory in November and December 2017 respectively. The comet was at a heliocentric distance greater than 3 au during both sets of observations. The images showed a well-developed tail with properties that suggested it was an ion tail. The spectra confirmed that we were observing well-developed bands of CO + and N + 2 . The N + 2 detection was unequivocally cometary a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 20 publications
3
48
2
Order By: Relevance
“…However, large N 2 abundances (>10%) are not expected either, unless there is a cometary outburst during the period of observation. Moreover, different observations have confirmed that the N 2 abundance in this comet is about 7% relative to CO (Cochran & McKay 2018;Biver et al 2018;Opitom et al 2019). Hence, we do not expect this comet to have a large enough N 2 abundance (>10%) to produce the observed [CI]/[NI] emission ratio.…”
Section: Effect Of the Neutral Species Abundancesmentioning
confidence: 68%
“…However, large N 2 abundances (>10%) are not expected either, unless there is a cometary outburst during the period of observation. Moreover, different observations have confirmed that the N 2 abundance in this comet is about 7% relative to CO (Cochran & McKay 2018;Biver et al 2018;Opitom et al 2019). Hence, we do not expect this comet to have a large enough N 2 abundance (>10%) to produce the observed [CI]/[NI] emission ratio.…”
Section: Effect Of the Neutral Species Abundancesmentioning
confidence: 68%
“…This fits with recent estimates of the CO snowline in the TW Hya disk (Zhang et al 2017). Appreciable amounts of N 2 in comets are rare (Cochran et al 2000;Cochran 2002;Rubin et al 2015), though a N 2 /CO ratio of 0.15 was recently reported in one comet (Cochran & McKay 2018), and the majority of comets therefore likely formed interior to the N 2 snowline, placing the N 2 snowline in the outer range of the proposed comet-forming region of 5 and 35 au (Mumma & Charnley 2011). Finally, Pluto appears to be rich in N 2 , which would be consistent with formation exterior to the N 2 snowline, though other explanations have been given as well (Stern et al 2018).…”
Section: Density and Temperature Structurementioning
confidence: 99%
“…The CN and UC images exhibited extended, filamentary structures similar to those seen with the CO + filter. Although the filters were designed to isolate gas (CN) or to be a nearly emission-free continuum area (UC), the CN bandpass includes N + 2 emission (Cochran and McKay 2018;Opitom et al 2019) and both bandpasses contain emissions from CO + ions (Pearse and Gaydon 1976, and references therein). For most comets, these ions are much fainter than the intended gas and/or continuum and can be safely ignored but this is not the case for R2 PanSTARRS.…”
Section: Dct-lmimentioning
confidence: 99%
“…d Due to the lack of observations of N2 in comets, the mean mixing ratios compared to H2O and CO are not meaningful to calculate. Therefore the number included is based on past observations discussed in Cochran and McKay (2018) and has very large uncertainty (indicated by the "?"). e Derived from our NH2 upper limit assuming all NH2 is released via NH3 photodissociation (i.e.…”
Section: Cometary Populationmentioning
confidence: 99%
See 1 more Smart Citation